Dynamics in Secondary Metabolite Gene Clusters in Otherwise Highly Syntenic and Stable Genomes in the Fungal Genus Botrytis. (14th October 2020) - Valero-Jiménez, Claudio A; Steentjes, Maikel B F; Slot, Jason C; Shi-Kunne, Xiaoqian; Scholten, Olga E; van Kan, Jan A L
Abstract: Fungi of the genus Botrytis infect >1, 400 plant species and cause losses in many crops. Besides the broad host range pathogen Botrytis cinerea, most other species are restricted to a single host. Long-read technology was used to sequence genomes of eight Botrytis species, mostly pathogenic on Allium species, and the related onion white rot fungus, Sclerotium cepivorum . Most assemblies contained <100 contigs, with the Botrytis aclada genome assembled in 16 gapless chromosomes. The core genome and pan-genome of 16 Botrytis species were defined and the secretome, effector, and secondary metabolite repertoires analyzed. Among those genes, none is shared among all Allium pathogens and absent from non- Allium pathogens. The genome of each of the Allium pathogens contains 8–39 predicted effector genes that are unique for that single species, none stood out as potential determinant for host specificity. Chromosome configurations of common ancestors of the genus Botrytis and family Sclerotiniaceae were reconstructed. The genomes of B. cinerea and B. aclada were highly syntenic with only 19 rearrangements between them. Genomes of Allium pathogens were compared with ten other Botrytis species (nonpathogenic on Allium ) and with 25 Leotiomycetes for their repertoire of secondary metabolite gene clusters. The pattern was complex, with several clusters displaying patchy distribution. Two clusters involved in the synthesis of phytotoxic metabolites are at distinct genomic locations in different Botrytis species. We provide evidence that the clusters for botcinic acid production in B. cinerea and Botrytis sinoallii were acquired by horizontal transfer from taxa within the same genus.